(untitled) - Burdea, Grigore C. (Hoboken, N.J., 2003)
Virtual reality is a very powerful and compelling computer application by which humans can interface and interact with computer-generated environments in a way that mimics real life and engages all the senses. Although its most widely known application is in the entertainment industry, the real promise of virtual reality lies in such fields as medicine, engineering, oil exploration and the military, to name just a few. Through virtual reality scientists can triple the rate of oil discovery, pilots can dogfight numerically-superior "bandits," and surgeons can improve their skills on virtual (rather than real) patients.
Keywords: Human-computer interaction,Virtual reality,Sự tương tác giữa con người và máy tính,Thực tế ảo